Polygenic risk of ischemic stroke is associated with cognitive ability. (16th February 2016) - Harris, Sarah E.; Malik, Rainer; Marioni, Riccardo; Campbell, Archie; Seshadri, Sudha; Worrall, Bradford B.; Sudlow, Cathie L.M.; Hayward, Caroline; Bastin, Mark E.; Starr, John M.; Porteous, David J.; Wardlaw, Joanna M.; et al.
Abstract : Objectives: We investigated the correlation between polygenic risk of ischemic stroke (and its subtypes) and cognitive ability in 3 relatively healthy Scottish cohorts: the Lothian Birth Cohort 1936 (LBC1936), the Lothian Birth Cohort 1921 (LBC1921), and Generation Scotland: Scottish Family Health Study (GS). Methods: Polygenic risk scores for ischemic stroke were created in LBC1936 (n = 1005), LBC1921 (n = 517), and GS (n = 6, 815) using genome-wide association study summary data from the METASTROKE collaboration. We investigated whether the polygenic risk scores correlate with cognitive ability in the 3 cohorts. Results: In the largest cohort, GS, polygenic risk of all ischemic stroke, small vessel disease stroke, and large vessel disease stroke, but not cardioembolic stroke, were correlated with both fluid and crystallized cognitive abilities. The highest correlation was between a polygenic risk score for all ischemic stroke and general cognitive ability ( r = −0.070, p = 1.95 × 10 −8 ). Few correlations were identified in LBC1936 and LBC1921, but a meta-analysis of all 3 cohorts supported the correlation between polygenic risk of ischemic stroke and cognitive ability. Conclusions: The findings from this study indicate that even in the absence of stroke, being at high polygenic risk of ischemic stroke is associated with lower cognitive ability.